How Volcanic Aerosols Globally Inhibit Precipitation - Zachary McGraw; Lorenzo M. Polvani (Geophysical Research Letters)
Abstract Volcanic aerosols reduce global mean precipitation in the years after major eruptions, yet the mechanisms that produce this response have not been rigorously identified. Volcanic aerosols alter the atmosphere's energy balance, with precipitation changes being one pathway by which the atmosphere acts to return toward equilibrium. By examining the atmosphere's energy budget in climate model simulations using radiative kernels, we explain the global precipitation reduction as largely a consequence of Earth's surface cooling in response to volcanic aerosols reflecting incoming sunlight. These aerosols also directly add energy to the atmosphere by absorbing outgoing longwave radiation, which is a major cause of precipitation decline in the first post‐eruption year. We additionally identify factors limiting the post‐eruption precipitation decline, and provide evidence that our results are robust across climate models.